Предмет: Алгебра,
автор: Vea
избавьтесь от иррациональности в знаменателе
Ответы
Автор ответа:
0
1(1+корень(2)+корень(3))=
(1+корень(2)-корень(3))(1+корень(2)-корень(3))(1+корень(2)+корень(3))=
=(1+корень(2)-корень(3))(1+2+2*корень(2)-3)=
=12*(1+корень(2)-корень(3))корень(2)=
=14*корень(2)*(1+корень(2)-корень(3))=
=14*(-корень(6)+корень(2)+2)
Ответ:(-корень(6)+корень(2)+2)4
Похожие вопросы
Предмет: Математика,
автор: koklod
Предмет: Английский язык,
автор: bikfazayev
Предмет: Русский язык,
автор: Аноним
Предмет: Математика,
автор: Аноним
Предмет: Физика,
автор: галечка